2023
DOI: 10.1101/2023.02.16.528781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal cortical dynamics for rapid scene recognition as revealed by EEG decoding

Abstract: The human visual system rapidly recognizes the categories and global properties of complex natural scenes. The present study investigated the spatiotemporal dynamics of neural signals involved in ultra-rapid scene recognition using electroencephalography (EEG) decoding. We recorded visual evoked potentials from 11 human observers for 232 natural scenes, each of which belonged to one of 13 natural scene categories (e.g., a bedroom or open country) and had three global properties (naturalness, openness, and roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…4, that style information characterizing surface perception strongly correlated with the VEPs within 200 ms after the stimulus onset, and that the visual impression of surface images were successfully reconstructed only by the VEPs via the MVAE models. These results are consistent with the fact that the global information processed in a single glance contributes to the rough perception of scenes and objects as well as natural surfaces (Potter, 1976; Thorpe et al 2001; Greene & Oliva, 2009; Greene & Hansen, 2020; Jagadeesh & Gardner, 2022; Orima & Motoyoshi, 2023).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…4, that style information characterizing surface perception strongly correlated with the VEPs within 200 ms after the stimulus onset, and that the visual impression of surface images were successfully reconstructed only by the VEPs via the MVAE models. These results are consistent with the fact that the global information processed in a single glance contributes to the rough perception of scenes and objects as well as natural surfaces (Potter, 1976; Thorpe et al 2001; Greene & Oliva, 2009; Greene & Hansen, 2020; Jagadeesh & Gardner, 2022; Orima & Motoyoshi, 2023).…”
Section: Discussionsupporting
confidence: 80%
“…The MVAE models developed in the present study reconstructed very high-quality visual stimuli from simple VEPs alone. However, the realistic images such as reconstructed images obtained in the present study were not generated by the VEPs for natural scene images (obtained in Orima & Motoyoshi, 2023). Previous studies have found that the perception of texture, including natural surface images used in the present study, is largely based on low-level statistical features such as image statistics (Bergen & Adelson, 1988; Heeger & Bergen, 1995; Zipser et al 1996; Portilla & Simoncelli, 2000; Baker & Mareschal, 2001; Motoyoshi et al 2007; Freeman & Simoncelli, 2011; Freeman et al 2013; Ziemba et al, 2019; Orima & Motoyoshi, 2021), but natural scenes have many aspects that cannot be explained by low-level features alone (Groen et al, 2013; Epstein & Baker, 2019; Greene & Hansen, 2020).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations